Perkembangan Konsep Pendidikan Bahasa Arab di Asia Tenggara - Ihsan Sa'dudin; Eka Safitri (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
Arabic education is a necessity for people who are Muslim. Islam is spread throughout the world including the Southeast Asian region. Southeast Asia, which includes the Philippines, Brunei Darussalam, Malaysia, Indonesia, Singapore and others who have a majority Muslim population. Islam entered the region peacefully, making it easier for development and its spread. The development and spread of Islam along with learning Arabic, because Arabic is the language of the Muslim holy book. However, the provision of education and learning in Arabic varies from country to country even though it is still in one region of Southeast Asia. The concepts of Arabic language education applied are strongly influenced by the state of government in these countries.